2018
DOI: 10.1007/s12079-018-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible reparative effect of low-intensity pulsed ultrasound (LIPUS) on injured meniscus

Abstract: Menisci are a pair of crescent-shaped fibrocartilages, particularly of which their inner region of meniscus is an avascular tissue. It has characteristics similar to those of articular cartilage, and hence is inferior in healing. We previously reported that low-intensity pulsed ultrasound (LIPUS) treatment stimulates the production of CCN2/CTGF, a protein involved in repairing articular cartilage, and the gene expression of major cartilage matrices such as type II collagen and aggrecan in cultured chondrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Our previous report revealed that CCN2 was increased in human chondrocytic cells by Dex 32 and in human chondrocytic and meniscus cells by LIPUS treatment. 10,11 Taken together, these findings indicate that Dex or LIPUS treatment in adipogenic cells increased CCN2 production at the mRNA and protein levels, similar to other cells, such as chondrocytes and meniscus cells. Although Dex was capable of inducing PPARγ (Figure 2), it did not induce adipogenesis per se; and LIPUS inhibited adipogenesis (Figure 1).…”
Section: Ablation Of the Effect Of Lipus On C3h10t1/2 Cells By Ccn2mentioning
confidence: 59%
See 2 more Smart Citations
“…Our previous report revealed that CCN2 was increased in human chondrocytic cells by Dex 32 and in human chondrocytic and meniscus cells by LIPUS treatment. 10,11 Taken together, these findings indicate that Dex or LIPUS treatment in adipogenic cells increased CCN2 production at the mRNA and protein levels, similar to other cells, such as chondrocytes and meniscus cells. Although Dex was capable of inducing PPARγ (Figure 2), it did not induce adipogenesis per se; and LIPUS inhibited adipogenesis (Figure 1).…”
Section: Ablation Of the Effect Of Lipus On C3h10t1/2 Cells By Ccn2mentioning
confidence: 59%
“…Previously, we reported that LIPUS treatment promotes CCN2 production in chondrocytes 10 and meniscus cells. 11 In addition, as we have reported that CCN2 promotes osteoblast differentiation, 23 we tested whether osteoblastic marker genes, such as Runx2, Sp7 (osterix) and Alpl (alkaline phosphatase), are upregulated by LIPUS treatment in adipocyte-committed C3H10T1/2 cells. As shown in Figure 1D panels d-f, LI-PUS treatment did not increase the expression of these osteoblastic marker genes.…”
Section: Inhibitory Effect Of Lipus On Adipogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The stagnation of vesicular trafficking would therefore enhance the basal ER stress and influence the proteoglycan release and accumulation. We have reported that CCN2 stimulates the mRNA expression of aggrecan in chondrocytic cells [1][2][3] and siRNA against the CCN2 down-regulated mRNA expression of aggrecan in chondrocytic cells [30,31]. However, Rab14 is a protein involved in intracellular membrane trafficking and not a signal inducer, so it is not surprising that Rab14 siRNA had no effect on ACAN mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently TUS was reported to improve function, tissue regeneration, and relieve pain via thermal and non-thermal mechanisms in osteoarthritis of the knee [33][34][35][36]. Experimental data suggest that TUS treatment might prevent degenerative changes of the meniscus and exert a reparative effect via activation of cartilage growth factors [37]. Despite such evidence of efficacy, to the best of our knowledge, TUS has never been studied in OAT.…”
Section: Introductionmentioning
confidence: 99%